Mechanisms and control of secretion in the Malpighian tubules of Tenebrio molitor : an immunohistochemical and electrophysiological study - Nicolson, Sue W. (University of Pretoria, 2013)
Thesis (DPhil (Zoology))--University of Pretoria, 2006.